Capsule-augmented scleral fixation of intraocular lenses - Soema Tebhla; Chaitra Jayadev; Rohita Nayak; Pragati Raj; Vedant Gambhir; Nagesha C Krishnappa (Indian Journal of Ophthalmology, 2025)
In-the-bag placement of intraocular lenses (IOLs) generally yields optimal results in terms of alignment and minimizes decentration or tilt. However, this approach can be counterproductive if the capsular bag is compromised, potentially leading to IOL malposition or inability to secure the lens. Repurposing the compromised capsular bag to its maximum potential can help place the initially intended IOL. This surgical series showcases techniques and options for scleral fixation of the same or a newer IOL, using the compromised bag as augmented support. The capsular bag provides alignment guidance, while scleral fixation stabilizes the IOL, thereby demonstrating a hybrid technique called capsule-augmented scleral fixation (CASF). This article provides a detailed description of CASF and explores its expanding applications in accommodating diverse IOL designs. This technique provides surgeons with an alternative when unexpected intraoperative challenges are encountered.